A study on spawning induction of Imbaw Anodontia edentula (Linne', 1758). - Bacaro, Teressa Mae D. (2008.)
The mud clam, Anodontia edentula, was induced to spawn using extract from ripe and developing gonads. Clams responded to the spawning stimulus by extension of the foot, swelling and extension of the mantle, swirling of the whole body, rapid opening and closing of the valves, ejecting of white material from the excurrent siphon and subsequent contraction of the adductor muscles. Successful spawning of all individuals occured with the use of gonad extract. Developing homogenized extract was not as effective in inducing the broodstock to spawn. Gametes were released through the excurrent siphon located at the posterior end.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Mud clam -- spawning -- Research; Anodontia edentula -- Research